2015
DOI: 10.1021/acs.orglett.5b01315
|View full text |Cite
|
Sign up to set email alerts
|

Homohalocyclization: Electrophilic Bromine-Induced Cyclizations of Cyclopropanes

Abstract: An efficient method for the halocyclization of cyclopropanes has been developed. The cyclopropanes undergo a 1,3-addition reaction to form homohalocyclization products compared to conventional alkene halocyclizations. The reaction can be induced by various electrophilic halogenating agents including 1,3-dibromo-5,5-dimethylhydantoin and N-iodosuccinimide. In cyclopropane derivatives with a preexisting stereocenter, excellent induced diastereoselectivities can be observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 52 publications
0
26
0
Order By: Relevance
“…Existing ring-opening reactions include oxidative addition into C–C bonds with transition metals, 6 8 oxidative 1,3-difunctionalization, 9 frustrated Lewis pairs, 10 , 11 or addition of strong nucleophiles 12 14 and mineral acids. 15 One-pot iodination/alkylation procedures are also known. 16 Our laboratory has begun to exploit the catalytically active aggregates formed between Brønsted acids and solvents such as hexafluoroisopropanol (HFIP) to enable challenging transformations.…”
Section: Introductionmentioning
confidence: 99%
“…Existing ring-opening reactions include oxidative addition into C–C bonds with transition metals, 6 8 oxidative 1,3-difunctionalization, 9 frustrated Lewis pairs, 10 , 11 or addition of strong nucleophiles 12 14 and mineral acids. 15 One-pot iodination/alkylation procedures are also known. 16 Our laboratory has begun to exploit the catalytically active aggregates formed between Brønsted acids and solvents such as hexafluoroisopropanol (HFIP) to enable challenging transformations.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Very recently Hennecke reported the cyclization of 1a using 1,3-dibromo-5,5-dimethylhydantoin (DBH) in the absence of catalyst. [5] As part of the research interests in Lewis base-catalyzed halocyclization reactions in our team, we reported aL ewis basic sulfide-catalyzed electrophilic bromocyclization of cyclopropylmethyl amide very recently. [6] In ap arallel research program, we are also studyingt he bromocyclizationo fc yclopropylcarboxylic acid 1.H owever, after examining the reactioncarefully it was found that such areaction could not proceed in the absence of light (vide infra, Table 1).…”
mentioning
confidence: 99%
“…Recently, Hennecke et al. reported a range of catalyst‐free halocyclization of cyclopropanes with tosylamides, hydroxyl, and carboxyl substituents, yielding the corresponding pyrrolidines, tetrahydrofurans and lactones, respectively . An emerging research direction involves the oxidative ring‐opening/functionalization of unactivated cyclopropanes using hypervalent iodine species…”
Section: Methodsmentioning
confidence: 99%